Word of mouth : the food you eat - Bontempo, Nancy Rogers; Stewart, Mark, 1960 July 7- (Chicago : Norwood House Press, 2012)
"One billion people on the planet do not get enough food every day. This book explores why this is everyone's problem, and helps readers understand how the global food supply is connected to environmental stress, as well as the science behind ensuring that food is safe and plentiful. An emphasis is placed on worldwide agricultural practices and innovations"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Food supply -- Juvenile literature; Agriculture -- Social aspects -- Juvenile literature